Moving toward Personalized Medicine in the Methadone Maintenance Treatment Program: A Pilot Study on the Evaluation of Treatment Responses in Taiwan. (16th December 2013) - Lee, Hsin-Ya; Li, Jih-Heng; Sheu, Yuh-Ling; Tang, Hsin-Pei; Chang, Wei-Chiao; Tang, Tze-Chun; Yeh, Yi-Chun; Wang, Shing-Yaw; Liu, Ray-H.
Abstract : This pilot study simultaneously evaluated the effects of various factors, including genetic variations of CYP2B6, CYP2C19, and ABCB1, demographic characteristics, disease states, methadone-drug interactions (MDIs), and poly-substance use, on the treatment responses among non-HIV patients in the methadone maintenance treatment program (MMTP) in Taiwan. A total of 178 patients were recruited from two major hospitals that provided MMTP services in southern Taiwan, and information regarding concomitant medications and diseases was acquired from the National Health Insurance (NHI) program. The results demonstrated that the methadone maintenance dose, CYP2B6 785G allele, and ABCB1 2677T allele have positive effects on the methadone plasma concentration. In contrast, patients with HCV coinfection, alcohol problems, and psychiatric diseases may have a negative response to treatment. Thus, a comprehensive evaluation of treatment responses in the MMTP should include not only genetic polymorphisms in methadone metabolism and transporter proteins, but also concomitant diseases, MDIs, and poly-substance use. The results also suggest that personalized medicine may be indispensable for a better outcome of the MMTP.